2017
DOI: 10.1016/j.jpainsymman.2016.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Dying Patients in the Nursing Home: Voices From Frontline Nursing Home Staff

Abstract: Context Nursing homes are an important site for end-of-life care, yet little is known about the perspectives of the frontline staff who provide a majority of this care. Objective To describe, from the staff perspective, positive/negative experiences related to caring for dying residents. Methods Qualitative analysis using survey data from staff working in 52 Indiana nursing homes. Results A total of 707 frontline staff who provide nursing, nurse aide, and social work services responded to open-ended prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
58
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 28 publications
3
58
0
1
Order By: Relevance
“…Previous studies have shown that people with dementia in a nursing home can suffer from the absence of relatives and caregivers at the end of life and can then, therefore, die in pain alone. This situation is ethically burdensome for nurses [39,40] and should be taken seriously by care management and policymakers who set the frameworks for care.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that people with dementia in a nursing home can suffer from the absence of relatives and caregivers at the end of life and can then, therefore, die in pain alone. This situation is ethically burdensome for nurses [39,40] and should be taken seriously by care management and policymakers who set the frameworks for care.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that patients at an NH can suffer from the absence of relatives and caregivers at the end-of-life and therefore, die in pain alone. This situation is ethically burdensome for nurses (37,38) and should be taken seriously by care management and policymakers setting the framework for care.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about quality of NH care and individuals' unhappiness with being in that setting, which serves as a safety net for people who do not have adequate support at home, may be reflected in these responses and thus not be a true measure of perceptions of the quality of hospice care provided. Also, the challenges of integrating hospice care into the NH setting have been described . Challenges with coordination of care plans or communication between hospice and NH staff can occur and could contribute to perceptions of poorer quality of care.…”
Section: Discussionmentioning
confidence: 99%